Desarrollo de una plataforma didáctica de simulación en tiempo real de un sistema de generación eléctrica compuesto por un aerogenerador de 400W y un inversor de potencia (2024)
In this project, it was developed a simulation’s platform of an electrical generation system which is composed of a 400 W wind turbine and a single phase inverter. The platform counts with software and hardware, these ones were coupled to build a scale microgrid. To begin with, the design and mathematical modeling of wind turbine. this was achieved using the numerical tools of MatLab and the OPAL-4510 rapid prototyping system. Subsequently, the design and validation of a proportional-integral (PI) control system was carried out so that at the output of the inverter the signal is AC alternating current with a frequency of 60 Hz and voltage magnitude of 120 V.